2005
DOI: 10.1007/s11274-005-9060-x
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi of teak leaves Tectona grandis L. and rain tree leaves Samanea saman Merr.

Abstract: In order to study the foliar endophytes from teak (Tectona grandis L.) and rain tree (Samanea saman Merr.) growing in the campus of Chulalongkorn University, healthy leaves were collected at two-monthly intervals during January to December. The number of genera and species, together with their colonization frequency (CF%) in mature teak and rain tree leaves were greater than those in the young leaves. More endophytic isolates in the leaves of both trees were recovered during the rainy season. The fungal genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 24 publications
9
41
0
1
Order By: Relevance
“…The above data corroborate results by Chareprasert et al (2006). They found the Phomopsis genus to be the most frequent endophyte fungus isolated from the leaves, both young and adult, of Tectona grandis L. and Samanea saman Merr.…”
Section: Discussionsupporting
confidence: 91%
“…The above data corroborate results by Chareprasert et al (2006). They found the Phomopsis genus to be the most frequent endophyte fungus isolated from the leaves, both young and adult, of Tectona grandis L. and Samanea saman Merr.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to the percentage of the isolates, the data are consonant with other findings showing that Phomopsis is quite frequently found as an endophyte in several plants (Chareprasert et al, 2006;Bernardi-Wenzel et al, 2010).…”
Section: G1-12supporting
confidence: 87%
“…Due to the pluviometric and relative humidity characteristics, it is possible that T. elegans was in the best conditions to afford the maximum colonization. Chareprasert et al (2006) stated that ripe leaves show a greater colonization by endophytes. The same was also found by other authors showing that endophytic colonization frequencies tend to increase indicating that rain, humidity and temperature can influence the occurrence of endophytes (Arnold and Herre, 2003;Chareprasert et al, 2006).…”
Section: Isolation Of T Elegans Endophytesmentioning
confidence: 99%
“…In the current study two sterile forms were isolated. Chareprasert et al (2006) found that Phomopsis was the most frequent endophytic fungus isolated from leaves, both young and adult, of Tectona grandis and Samanea saman Merr. Similarly, in the present study, Phomopsis spp.…”
Section: Discussionmentioning
confidence: 98%